Hindi Dalit Literature and the Politics of Representation. - Hunt, Sarah Beth (Routledge India, 2014)
This study explores how Dalits in north India have used literature as a means of protest against caste oppression. Including fresh ethnographic research and interviews, it traces the trajectory of modern Dalit writing in Hindi and its pivotal role in the creation, rise and reinforcement of a distinctive Dalit identity. The book challenges the existing impression of Hindi Dalit literature as stemming from the Dalit political assertion of the 1980s and as being chiefly imitative of the Marathi Dalit literature model. Arguing that Hindi Dalit literature has a much longer history in north India, i.